Enterprise Surveys : Philippines Country Pofile 2015 - World Bank (World Bank, Washington, DC, 2017)
The Enterprise Surveys (ES) focus on many aspects of the business environment. These factors can be accommodating or constraining for firms and play an important role in whether an economy’s private sector will thrive or not. An accommodating business environment is one that encourages firms to operate efficiently. Such conditions strengthen incentives for firms to innovate and to increase productivity — key factors for sustainable development. A more productive private sector, in turn, expands employment and contributes taxes necessary for public investment in health, education, and other services. Questions contained in the ES aim at covering most of the topics mentioned above. The topics include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, access to finance, innovation, labor, and perceptions about obstacles to doing business. The ES are conducted by the World Bank Group and its partners across all geographic regions and cover small, medium, and large firms.The surveys are administered to a representative sample of firms in the non-agricultural, formal, private economy. The ES are repeated approximately every four years for a particular economy (or region). By tracking changes in the business environment, policymakers and researchers can look at the effects of policy and regulatory reforms on firm performance. This document summarizes the results of the Enterprise Survey for the Philippines.